EFEKTIFITAS PERBEDAAN KOMPRES HANGAT DAN DINGIN TERHADAP PERUBAHAN SUHU TUBUH PADA ANAK DI RSUD DR. M. YUNUS BENGKULU - Rahmawati, Ida; Purwanto, Doby (Universitas Tribhuwana Tunggadewi, 2020)
Cases of fever due to infection in the world have increased every year. Temperatures above 38 ° C often cause seizures and death. Nursing intervention is needed in an effort to reduce fever in children. This study aims to study the effectiveness of giving warm and cold compresses to changes in body temperature in children in the edelweiss room Dr. M. Yunus Bengkulu. The study design uses a quasi-experimental design with two groups pretest postest design. The population in this study were all pediatric patients who experienced an increase in body temperature in Edelweis Room Dr. M. Yunus Bengkulu. The number of samples is 30 people with accidental sampling technique. The normality test uses the Shapiro-Wilk test. Statistical test uses independent t-test. Warm compress normality test obtained P value = 0.052> 0.05. Cold compress normality test obtained a value of P = 0.050 = 0.05 which means that all data are normally distributed. T-test results of two samples obtained value of t = -2.030 is priced to be t = 2.030 with P-Value = 0.029